Rhigognostis erysiphaea (Meyrick, 1938) comb. nov. (Lepidoptera, Plutellidae), with description of male and female genitalia - Baraniak, Edward; Stüning, Dieter; Walczak, Urszula (Zootaxa, 2015)
A new combination, Rhigognostis erysiphaea (Meyrick, 1938) is proposed. The species is re-described with a photo of the type specimen. The male and female genitalia are described and illustrated for the first time.